Mercantilismo y crecimiento económico en el virreinato del Perú. El estanco del tabaco 1750 - 1800 - Morales Cerón, Carlos (2012)
Conform he was leaving extending in the Peru the real interventionism for intermission of the Bourbon reforms, an economic growth maintained that he benefitted the cost-reducing forces of the country was produced. The colonial politics under the state impulse began to yield its consequences, which were shown at the indexes of collection that the national treasury was showing. In this process the State kept an important role like intervening businessman the control of the commerce of the tobacco that it enabled strengthening economic growth. The low interventionism his mercantilist mode took place for the fiscal crisis and they enabled the illicit trade that presented the shopping district of tobacco, the results of the process surpassing the problems generated by the liberal phase of the Bourbon reforms.